2006
DOI: 10.1016/j.jalgebra.2006.06.043
|View full text |Cite
|
Sign up to set email alerts
|

On the Goldie dimension of rings and modules

Abstract: We find a bound for the Goldie dimension of hereditary modules in terms of the cardinality of the generating sets of their quasi-injective hulls. Several consequences are deduced. In particular, it is shown that every finitely generated hereditary module with countably generated quasi-injective hull is noetherian. It is also shown that every right hereditary ring with finitely generated injective hull is right artinian, thus answering a long standing open question posed by Dung, Gómez Pardo and Wisbauer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Modul herediter merupakan perumuman dari gelanggang herediter, pertama kali diperkenalkan oleh Shrikhande [10] pada tahun 1973. Studi tentang modul herediter atas gelanggang telah banyak dilakukan seperti dapat dilihat pada [5,7].…”
Section: Pendahuluanunclassified
“…Modul herediter merupakan perumuman dari gelanggang herediter, pertama kali diperkenalkan oleh Shrikhande [10] pada tahun 1973. Studi tentang modul herediter atas gelanggang telah banyak dilakukan seperti dapat dilihat pada [5,7].…”
Section: Pendahuluanunclassified
“…We consider the special case in which the given ring R is left hereditary and we try to find conditions on its cotorsion envelope which ensure that R is semilocal. These conditions are inspired by [5]. In that paper, authors showed that any left hereditary ring having a countably generated left injective envelope is left noetherian.…”
mentioning
confidence: 99%
“…In particular, we deduce that left hereditary rings with finitely generated left cotorsion envelope are just the left hereditary left cotorsion semiperfect rings, thus obtaining the structure of them. We would like to stress that our proof relies on set theoretical arguments which have their origin in the decomposition of infinite sets into almost disjoint subsets obtained by Tarski in [18,Théorème 7] and that were also used in [5,15] to obtain their main results. However, the situation here is much more difficult to handle since we do not have unique cotorsion envelopes of pure submodules of C = C ( R R) within C .…”
mentioning
confidence: 99%
See 1 more Smart Citation